Partial resolution of acute interstitial pneumonia in native lung after single lung transplantation. Issue 11 (November 1996) - Robinson, D S; Geddes, D M; Hansell, D M; Shee, C D; Corbishley, C; Murday, A; Madden, B P
Abstract : The case of a 49 year old man presenting with rapidly progressive interstitial lung disease is described. Radiological findings and the lung biopsy specimen were compatible with an acute interstitial pneumonia, as was the relentless clinical course culminating in hypoxic respiratory failure. After right single lung transplantation there was considerable improvement in lung function and radiographic clearing of disease in the native left lung.